Neuroprotective effects of remote limb ischemic preconditioning through enhanced cerebral blood flow via activation of the PI3K/AKT pathway in ischemic stroke - Dou, Chaoran; Tang, Diwen; Yan, Yulin; Shui, Wen; Zhou, Minzhi; Chen, Bin; Feng, Lishuai; Li, Benhao; Ying, Tao (View (Beijing, China), 2025)
Acute ischemic stroke (AIS) remains a leading cause of mortality and disability worldwide. A key barrier to recovery is the inadequate restoration of cerebral blood flow following vascular recanalization. This study demonstrates the therapeutic efficacy of remote limb ischemic preconditioning (RLIPC) for AIS, utilizing advanced multimodal imaging techniques to visualize its effects and elucidate underlying mechanisms. In human volunteers, RLIPC modulated cerebral perfusion and reduced the arterial resistivity index, as assessed by noninvasive Transcranial Doppler ultrasound. In a rat model of middle cerebral artery occlusion/reperfusion (MCAO/R), ultrasound localization microscopy (ULM) enabled high‐resolution visualization of regional perfusion, revealing that RLIPC significantly enhanced blood flow within the M4 and M5 branches of the MCA during the hyperacute phase. RLIPC also reduced infarct volume and neuronal apoptosis, and further promoted neovascularization in the subacute and chronic stages. Importantly, behavioural assessments confirmed RLIPC's long‐term benefits on motor and cognitive function. Using ultra‐high field magnetic resonance imaging, we demonstrate for the first time that RLIPC confers neuroprotection by enhancing glymphatic clearance and neural conduction. Mechanistic studies revealed RLIPC‐mediated activation of the PI3K/AKT pathway, associated with upregulated expression of anti‐apoptotic (BCL2A1), angiogenic (HIF‐1α, VEGF), and neuroprotective (BDNF) genes. Our findings indicate that RLIPC holds significant therapeutic promise for ischemic stroke and potentially other neurological disorders.